Direct Access to N‐Unprotected α‐ and/or β‐Tetrasubstituted Amino Acid Esters via Direct Catalytic Mannich‐Type Reactions Using N‐Unprotected Trifluoromethyl Ketimines. Issue 67 (26th September 2017) - Sawa, Masanao; Morisaki, Kazuhiro; Kondo, Yuta; Morimoto, Hiroyuki; Ohshima, Takashi
Abstract: Direct catalytic C−C bond‐forming addition to N‐unprotected ketimines is an efficient and straightforward method of synthesizing N‐unprotected tetrasubstituted amines that eliminates prior protection/deprotection steps and allows facile transformation of the products. Despite its advantages, however, N‐unprotected ketimines have difficulties in C−C bond‐forming reactions, and only a limited number of reactions and substrates are reported compared with their N‐protected counterparts. Herein we report that N‐unprotected trifluoromethyl ketimines are effective for C−C bond‐forming reactions using Mannich‐type reactions as a model case. We demonstrate that Lewis acid catalysis was effective for promoting reactions with various N‐unprotected trifluoromethyl ketimines, and thiourea organocatalysis was effective for promoting highly enantioselective reactions with various carbonyl nucleophiles, providing direct access to various N‐unprotected α‐ and/or β‐tetrasubstituted amino acid esters. Furthermore, direct construction of vicinal tetrasubstituted chiral carbon stereocenters was achieved for the first time in a highly enantio‐ and diastereoselective manner. These results demonstrate the potential of N‐unprotected ketimines as substrates applicable to many other addition reactions. Abstract : Imine it this time : N‐unprotected trifluoromethyl ketimines as effective electrophiles for direct catalytic Mannich‐type reactions are reported. The first stereoselective construction of vicinal tetrasubstituted carbon stereocenters with N‐unprotected ketimines is also presented.